FEATURES OF THE LANGUAGE ABSURDITY PRAGMATICS TRANSMITTING IN THE TRANSLATION - E. Yakovleva (Гуманитарные и юридические исследования)
The article is devoted to understanding and describing of the phenomenon of linguistic absurdity from the perspective of pragmalinguistics and translation theory. The author focuses special attention on the dificulties of translating a literary text in terms of transmitting the pragmatics of linguistic absurdity. Since the absurdity presupposes the preservation of the author's intention, it is important for a translator to explain to a reader of the target language the incomprehensible cultural realities, speech stereotypes, word-play, etc., using standard and common vocabulary of the language to be translated. The main content of the study is an analysis of the stories "In His Own Write" (1964) and "Spaniard in the Works" (1965), authored by John Lennon, from the point of view of language absurdity and its main functions. A detailed study of this phenomenon has shown that linguistic absurdity performs mainly a gaming function, which is determined by the author's intention, based on the main tasks of the literary type of texts and created mainly with the help of a wordplay. The main goal of the gaming absurdity (found in 67 % of examples of our empirical material) is to create a certain aesthetic effect. To preserve the pragmatics of the source text, the translator A. A. Kurbanovsky often resorts to the use of occasional conformity with elements of additions, being guided by the principle of sound similarity. Analysis of examples of functioning in the text of destructive language absurdity (the second most frequent function of the absurdity, identified in the analyzed texts, is 33%) and their translation allowed us to conclude that this type of absurdity is created mainly with the help of semantic substitution, less often by means of semantic contamination. It is evident that in order to preserve the pragmatics of the source text, translational transformations are applied based on both the linguistic and extra-linguistic context, and the preservation and transmission of the pragmatic potential of statements is achieved by means of zero transformation, sometimes translation techniques of addition or omission are used.